Formulación plan de marketing digital de la Facultad de Ciencias Económicas y Administrativas para el año 2024 (2024)
This thesis focuses on a comprehensive analysis of the Facultad de Ciencias Económicas y Administrativas (FCEA) of the Universidad de Ibagué, with the purpose of developing a robust digital marketing plan for the year 2024, in order to strengthen and empower the faculty. Evaluating both the external and internal environment, areas for improvement and opportunities for growth are identified, highlighting educational quality as a strength. Strategies are proposed to improve innovation and marketing, with emphasis on the creation of educational and cutting-edge content, targeted digital advertising campaigns and improvements in the online user experience. This approach seeks to increase FCEA's visibility and reputation, as well as attract and retain potential students, laying the necessary foundation for its continued development and success.